Copper Oxide/Functionalized Graphene Hybrid Nanostructures for Room Temperature Gas Sensing Applications - Monika Gupta; Huzein Fahmi Hawari; Pradeep Kumar; Zainal Arif Burhanudin (Crystals, 2022)
Oxide semiconductors are conventionally used as sensing materials in gas sensors, however, there are limitations on the detection of gases at room temperature (RT). In this work, a hybrid of copper oxide (CuO) with functionalized graphene (rGO) is proposed to achieve gas sensing at RT. The combination of a high surface area and the presence of many functional groups in the CuO/rGO hybrid material makes it highly sensitive for gas absorption and desorption. To prepare the hybrid material, a copper oxide suspension synthesized using a copper acetate precursor is added to a graphene oxide solution during its reduction using ascorbic acid. Material properties of the CuO/rGO hybrid and its drop-casted thin-films are investigated using Raman, FTIR, SEM, TEM, and four-point probe measurement systems. We found that the hybrid material was enriched with oxygen functional groups (OFGs) and defective sites, along with good electrical conductivity (Sheet resistance~1.5 kΩ/□). The fabricated QCM (quartz crystal microbalance) sensor with a thin layer of the CuO/rGO hybrid demonstrated a high sensing response which was twice the response of the rGO-based sensor for CO2 gas at RT. We believe that the CuO/rGO hybrid is highly suitable for existing and future gas sensors used for domestic and industrial safety.